Risk of adverse perinatal outcomes among women with clinical and subclinical histopathological chorioamnionitis - Olguín-Ortega, Andrea; Figueroa-Damian, Ricardo; Palafox-Vargas, Martha Leticia; Reyes-Muñoz, Enrique (Frontiers in Medicine, 2024)
This historical cohort study aimed to assess the risk of adverse perinatal outcomes (APOs) in pregnant women with histologic chorioamnionitis (HCA). During the study period, all placentas were evaluated by a perinatal pathologist, and all women with HCA were included. Two groups were integrated: 1) women with clinical chorioamnionitis (CCA) and 2) women with subclinical chorioamnionitis (SCCA). Additionally, we conducted a secondary analysis to compare the prevalence of APOs among stage 1, 2 and 3 of HCA and the risk of APOs between grades 1 and 2 of HCA. The APOs analyzed were preterm birth, stillbirth, neonatal weight <1500g, neonatal sepsis. Relative risk with 95% confidence interval was calculated. The study included 41 cases of CCA and 270 cases of SCCA. The mean gestational age at diagnosis and birth was 30.2 ± 5.4 weeks and 32.5 ± 5.1 weeks, for group 1 and 2, respectively. The study also found that women with HCA stage 3 and grade 2 had a higher prevalence and risk of adverse perinatal outcomes. The findings of this study suggest the importance of placental histological study to excluded SCCA, which represents a significant risk to both maternal and neonatal health, contributing to high morbidity and mortality.